Effect of Gingival Biotype on the Progression of Periodontal Disease - Mranali K Shetty; Neetha J Shetty (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: The causes that interfere with the outcome of dental treatment is gingival biotypeScalloped –thin and flat-thick are the types of gingival biotypes. Periodontal diseases progress differentlyin response to plaque associated inflammation. While periodontal pocket may be the result in flat thickgingival biotype , gingival recession may be the result of scalloped and thin gingival biotype. With thisbackground this study aimed at evaluating the relation between gingival biotype and the progression ofperiodontal diseases .Materials and Methods: Sixty systemically healthy subjects between 30-50years of age, diagnosedwith chronic periodontitis who visited outpatient department of Manipal college of dental sciences,Mangalore, India, took part in the study. The subjects were explained about the study, and writtenconsent was obtained. A thorough dental examination with a comprehensive survey of maxillary centralincisors and lateral incisors was performed to assess the following clinical parameters: Bleeding onprobing, probing pocket depth, loss of attachment, gingival thickness and gingival recession . Thecollected data was subjected to statistical analysis.Results: The mean Gingival thickness for the central incisor, lateral incisor, and canine were 1.11 mm,1.01 mm, and 0.82 mm, respectively. ANOVA test was done to compare the gingival thicknessbetween the incisors which was statistically significant with a value < 0.001. The PosthocTukey tests comparing gingival recession showed a mean difference of 1.324* and wasstatistically significant with a p value of < 0.001. Comparison of probing pocket depth showeda mean difference of 0.882* which again was statistically significant with a p value of < 0.001.